The Contestation of Profanity and Sacral at Taman Bungkul Landscape - Rohma Tunurus Asholiha; Lina Puryanti (Dirasah International Journal of Islamic Studies, 2023)
Since its inauguration in 2007, the development of Bungkul Park has been very conspicuous from a tomb to a tourist attraction. As a historical place, Bungkul Park is not as famous as Wali Songo. Geographically, the tomb of Sunan Bungkul and the green open space's Bungkul border the wall to distinguish the location's layout. This place is better known as a recreational place. Changes in function are more creative than religious. This study tries to answer (1) How is the Sacred culture that occurs in religious tourism? (2) How is the Profan culture in the bungkul ParkPark? (3) What is the impact of cultural differences in religious tourism in Sunan Bungkul and Bungkul Park? These problems are explained by analyzing the data and sources obtained through the stages of qualitative descriptive research methods, which include ethnography, criticism, interpretation, and historiography. Based on the data analysis and sources received, the development of Bungkul Park, which is getting better, brings the Surabaya city government to revitalize Bungkul Park. The City Government should pay more attention to the religious aspect than the profane aspect of using Bungkul. This is because of Bungkul's care, most of which pays more attention to the ParkPark than his burial. Visitors are also more familiar with the ParkPark than bungkul's tomb.